Information Technology Audit at LKP FARAFI Using the Cobit 2019 Framework - Anisa, Livia Nur; Syaputra, Muhammad Adie (Universitas Mohammad Husni Thamrin, 2025)
In the era of globalization, IT infrastructure needs to be supported by an evaluation system where the evaluation is needed to assess and consider whether the work processes that have been implemented are feasible or need further improvements. This study aims to conduct an information technology governance audit at LKP FARAFI using the COBIT 2019 framework with a focus on two process domains, namely DSS01 (Manage Operations) and DSS06 (Manage Business Process Controls). At LKP FARAFI there are problems in the activities of managed human resources and managed data. To ensure the process runs smoothly, the researcher conducted an audit process with the stages of Literature Study, Interviews and Questionnaires. This audit was motivated by problems in data management and human resources that are not optimal. The data analysis methods used in this study are Opportunity Analysis and GAP Analysis. The IT processes used are DSS01 and DSS06. The measurement results show that the level of process capability in the DSS01 and DSS06 domains is still at level 1 (Performed Process), while the expected level is level 4 (Quantitatively Managed Process). The average GAP in the DSS01 process was 2.66 and DSS06 was 2.48, indicating a significant gap between the existing and target conditions. Based on the results of the study, recommendations were given to improve the IT capabilities at LKP FARAFI, which currently reaches level 1.